Language and Communication Implications of Artificial Intelligence on Selected Nigerian University Undergraduates - OBASI, Jane Chinelo; OBIEKWE, Ekene Blessing (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
In recent times, the emergence of artificial intelligence has had a tremendous influence on human language and communication. It involves developing computer programmes to complete tasks which would otherwise require human intelligence. This study, therefore, investigates the impact of artificial intelligence on the English language use and communication skills of selected Nigerian university undergraduates. Questionnaires were designed using a five-point rating scale and shared with one hundred and fifty respondents from the University of Nigeria, Nsukka and the University of Nigeria, Enugu Campus. These students were randomly sampled because they were selected without having any particular choice in mind. All the responses gathered through an online SurveyMonkey survey were categorised and analysed qualitatively and quantitatively. Albert Bandura’s (1977) Social Learning Theory was adopted as the theoretical framework for this study. The findings show that artificial intelligence impacts the language and communication of Nigerian undergraduates both positively and negatively, and this includes, among others, improvement of their vocabulary and grammar, and overdependence on AI technology for English language vocabulary development.